Poisoner in chief : Sidney Gottlieb and the CIA search for mind control - Kinzer, Stephen (Henry Holt and Company, 2019)
The visionary chemist Sidney Gottlieb was the CIA<U+2019>s master magician and gentlehearted torturer<U+2015>the agency<U+2019>s “poisoner in chief.” As head of the MK-ULTRA mind control project, he directed brutal experiments at secret prisons on three continents. He made pills, powders, and potions that could kill or maim without a trace<U+2015>including some intended for Fidel Castro and other foreign leaders. He paid prostitutes to lure clients to CIA-run bordellos, where they were secretly dosed with mind-altering drugs. His experiments spread LSD across the United States, making him a hidden godfather of the 1960s counterculture. For years he was the chief supplier of spy tools used by CIA officers around the world. Stephen Kinzer, author of groundbreaking books about U.S. clandestine operations, draws on new documentary research and original interviews to bring to life one of the most powerful unknown Americans of the twentieth century. Gottlieb<U+2019>s reckless experiments on “expendable” human subjects destroyed many lives, yet he considered himself deeply spiritual. He lived in a remote cabin without running water, meditated, and rose before dawn to milk his goats.